2020
DOI: 10.1111/jan.14289
|View full text |Cite
|
Sign up to set email alerts
|

Structural empowerment is a strong predictor of organizational commitment in nurses: A systematic review and meta‐analysis

Abstract: Aims The aim of this systematic review and meta‐analysis is to explore the relationship between structural empowerment and organizational commitment and to examine a theoretical model under which empowerment could potentially affect organizational performance. Design PRISMA guidelines for systematic reviews and meta‐analyses were used and quality assessment of articles was performed. Data sources Electronic database searches were conducted in Google Scholar, PubMed/Medline, CINAHL, Scopus, and EMBASE from Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
79
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(85 citation statements)
references
References 117 publications
(212 reference statements)
3
79
0
3
Order By: Relevance
“…Thus, the empowerment of nurses contributes to greater professional satisfaction, decreased burnout rates, and increased autonomy and organizational commitment. In addition, it positively impacts patient safety and quality of care in the health services ( 3 - 4 , 6 - 8 ) . As a result, it is necessary for the managers to be attentive to their organizational practices, since just ensuring the quality of the technical aspects of processes or services is no longer sufficient to maintain the efficiency of organizations, and it is also necessary to invest in the involved people ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the empowerment of nurses contributes to greater professional satisfaction, decreased burnout rates, and increased autonomy and organizational commitment. In addition, it positively impacts patient safety and quality of care in the health services ( 3 - 4 , 6 - 8 ) . As a result, it is necessary for the managers to be attentive to their organizational practices, since just ensuring the quality of the technical aspects of processes or services is no longer sufficient to maintain the efficiency of organizations, and it is also necessary to invest in the involved people ( 9 ) .…”
Section: Introductionmentioning
confidence: 99%
“…6,62 Available research supports the positive association between worker engagement and job resources, 66 and structural empowerment is a positive predictor for psychological empowerment. [67][68][69][70][71] Adequate job resources increase the likelihood that employees will feel engaged, 72 and engaged employees more often participate actively in their workplaces than unengaged employees. 26 Building on these findings, our study has revealed strong positive and significant correlations between nurse empowerment and engagement and between nurse empowerment and teamwork.…”
Section: Discussionmentioning
confidence: 99%
“…Theories of empowerment touch the "power" field and need to be complemented with theories of structural power relations involving both formal and informal power (11,12). This may also yield results from WHP projects as structural empowerment is strongly correlated to health dimensions such as organizational commitment and psychological empowerment in public health care organizations (39). Thus, considering structural empowerment in organizational WHP program support increased effective workplace culture and organizational performance.…”
Section: Discussionmentioning
confidence: 99%